Oldenlandia vasudevanii (Spermacoceae, Rubiaceae) a new species from the Southern Western Ghats, India - Soumya, Murugan; Sojan, Jose; Suresh, Veerankutty; Nair, Maya Chandrasekharan (Phytotaxa, 2017)
The new species Oldenlandia vasudevanii from the Southern Western Ghats, Palakkad, Kerala, India, is described and illustrated. The species differs from its allied species O. stocksii and O. hygrophila in terms of stout pedicel, calyx lobes exceeding the level of corolla, number of stipules, number of accessory calyx teeth, and size of the corolla tube. Description of taxa with distribution, ecology and comparison among allied taxa has been provided.